2007
DOI: 10.3171/jns.2007.106.6.1051
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of patient-specific numerical simulation of cerebal aneurysm hemodynamics to inflow boundary conditions

Abstract: Measurement of the blood flow rate as well as the distribution of the flow rates in the patient's feeding arteries may be needed for numerical simulations to accurately reproduce the intraaneurysmal hemodynamics in a specific aneurysm in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 19 publications
2
57
1
Order By: Relevance
“…The impact on hemodynamic indices was not addressed in that study, and for our HR simulations, the average element side length in the aneurysm sac was 0.06 mm, well below the 0.08 mm reported for the converged solutions of Hodis et al 8 The pronounced impact of the CFD solution strategy on the magnitude of derived hemodynamic indices implies that the solution strategy must be acknowledged as an additional source of variability, especially if and when the findings of different groups, potentially using a wide range of strategies, are compared or analyzed together. In striving for more patient-specific simulations, most studies have focused on the impact of other assumptions or uncertainties such as inflow/outflow conditions, 31 non-Newtonian rheology, 32 compliance, 33 and choice of imaging technique. 34,35 Although it is difficult to draw a direct comparison between their findings and the results of the present study, inspection of figures from those studies suggests that the qualitative differences due to those assumptions are less than the differences due to choice of CFD solution strategy as demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on hemodynamic indices was not addressed in that study, and for our HR simulations, the average element side length in the aneurysm sac was 0.06 mm, well below the 0.08 mm reported for the converged solutions of Hodis et al 8 The pronounced impact of the CFD solution strategy on the magnitude of derived hemodynamic indices implies that the solution strategy must be acknowledged as an additional source of variability, especially if and when the findings of different groups, potentially using a wide range of strategies, are compared or analyzed together. In striving for more patient-specific simulations, most studies have focused on the impact of other assumptions or uncertainties such as inflow/outflow conditions, 31 non-Newtonian rheology, 32 compliance, 33 and choice of imaging technique. 34,35 Although it is difficult to draw a direct comparison between their findings and the results of the present study, inspection of figures from those studies suggests that the qualitative differences due to those assumptions are less than the differences due to choice of CFD solution strategy as demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated the significant influence of BCs on computed hemodynamic indices. 9,19,44 Depending on the method of derivation, BCs can be broadly divided into two categories; those that are patient-specific and those that are non-patient-specific. …”
Section: Discussionmentioning
confidence: 99%
“…9,19,44 Unfortunately, these are rarely available. Of 24 articles reviewed for this study (Table 3), only 6 (25%) used patient-specific BCs.…”
Section: Patient-specific Bc'smentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high-resolution 3D geometry and patient-specific measurements of local flow velocities in the afferent artery as boundary conditions for hemodynamic simulations were used. [13][14][15] …”
mentioning
confidence: 99%